GW24-e3139 A new training program on the blood lactate level of type 2 diabetes. (1st October 2013) - Jing, Cheng; Fan, Zheng; Suixin, Liu
Abstract : Objectives: The present study is to investigate the clinical significance of blood lactate level in type 2 diabetes and the effectiveness of aerobic training combined with resistance training therapy for type 2 diabetes. Methods: 80 type 2 diabetes outpatients with no complications and another 20 normal healthy people were recruited to observe the relationship between blood lactate level and type 2 diabetes. Then 38 of these 80 type 2 diabetes outpatients were subdivided into two groups randomly: the conventional therapy group (N = 22) and the advanced exercise therapy group (N = 16). The conventional therapy includes regular medication plus the guidance of diet and exercise, while the advanced exercise therapy adds aerobic training combined with resistance training (8 weeks, 36 sessions in total) besides the conventional therapy. Each exercise session includes: aerobic training at an intensity of 60−80% HRR (Heart Rate Reserve) lasting for 30−45 minutes (6 times/week during the first 4 weeks and 3 times/week during the last 4 weeks), and the following resistance training at the intensity of 50−55% 1RM (one Reception Maximum) for 15−30 minutes (3 times/week, 8 weeks). All the groups were asked to take the tests of fasting blood glucose (FBG) level, 2-hour postprandial blood glucose (PBG) level, fasting insulin (FIN) level, postprandial plasma Insulin (PIN) level, total cholesterol (TC) level, high density lipoprotein (HDL) level, glycated haemoglobin (HbA1c) level, insulin resistance index (IRI) level and blood lactate (Lac) level before and after the intervention. Results: (1) The Lac level of diabetic group was significantly higher than normal control group (P <0.01). (2) After the 8-week therapy, the FBG, PBG, PIN, HbA1c, Lac and IRI levels of both conventional therapy group and advanced exercise therapy group were significantly decreased (P < 0.01). The FIN level of the advanced exercise group was significantly decreased (P < 0.01) after the advanced exercise therapy, but no change in the conventional therapy group. (3) After the 8-week therapy, PBG, PIN, HbA1c, Lac and IRI levels of the advanced exercise group were significantly decreased (P < 0.01 or P < 0.05) compared with the conventional therapy group. Conclusions: (1) Blood lactate level could be used as a new clinical indicator for the type 2 diabetes. (2) The advanced exercise therapy (aerobic training combined with resistance training) is recommended for type 2 diabetes.